Problems and Perspectives of BRICS Countries Transfer to “Green Economy” and Law-carbon Energy Industry - Dudin, Mihail Nikolaevich; Frolova, Ð•vgenia Ð•vgenevna; Artemieva, Julia Alexandrovna; Bezbah, Vitaliy Vasil’evich; Kirsanov, Alexey Nikolaevich (International Journal of Energy Economics and Policy, 2016)
This article states basics of the “green economy” concept and the role of transferring from industrial to ecologically responsible development of renewable power sources. The main aim of this article is to determine principle regularities that stipulate and restrict abilities of the BRICS countries to use the renewable energy sector in order to replace high-carbon consumption in economic and social sector. Basic conclusions of this work are the following: 1) The aggregate of economic, social, ecological, and energetic problems faced by the modern civilization are directly interrelated. That is why in order to preserve the environment and natural resources for future generations, it is necessary to refuse from resources of unsustainable and high-carbon areas of development. 2) The concept of green economy lies in the fact that needs of the humankind must be rationalized, above all, in the power context, through ensuring a reasonable refusal from using economically destructive carbons by replacing them with renewable power sources. 3) A lot of European countries made the power breakthrough simultaneously developing traditional and renewable energetic. However, it is impossible to make the same conclusion in relation to the BRICS countries. In the BRICS coalition only one country – China - can be acknowledged as a leader in using the renewable energy sector. However, at the same time this country is an “anti-leader” in polluting the environment. 4) At the present time economy of the BRICS countries cannot be yet acknowledged as green. However, along with this, India, China, RSA, Russia, and Brazil have a considerable natural, climatic, and geographical potential for efficient use of benefits of the renewable energy sector. In the future it will allow them to transfer from the industrial and unsustainable vector of development to ecologically responsible development. Keywords: green economy, low-carbon economy, renewable energy sector, BRICS, European Union, power resources, stable development JEL Classifications: Q57, Q28